Concept "feng shui" as a word of Chinese origin in the consciousness of native Russian language (based on the psycholinguistic experiments) - Yang Xi (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2016)
This article studies one borrowing from Chinese – «feng shui» with the standpoint of cognitive science and psycholinguistics. According to the statistics from «The Russian National Corpus», «YandexNews» and our experiments we can conclude that this borrowing «feng shui» is quite common in Russian language. We expand research based on the theory and method of Russian linguists: Z.D. Popova and I.A. Sternin, implying three steps for description of concept «feng shui»: 1) describe macrostructure of concept; 2) describe categorical structure of concept; 3) describe field organization of concept. According to the data of psycholinguistic experiments we can point out not only the adaptive information of «feng shui» among Russianspeakers, but also concept content. Associative experiments create a concept model of «feng shui», and divide it into the core, proximal, distal and the extreme periphery.